THE INFLUENCE OF MENU VARIETY AND FOOD QUALITY ON CONSUMER SATISFACTION AT PRATA WAROENG 8 TIBAN, BATAM - Gunawan, Agung Arif; Novriana, Lufita Devi; Syaiful, Hendra (JURNAL MANAJEMEN KULINER, 2025)
This study aims to determine the phenomena that occur in Prata Waroeng 8 that affect the level of consumer satisfaction. One of them is a misunderstanding between the dishes ordered and the dishes served. The location of this study is at Prata Waroeng 8 Tiban, Batam City, Riau Islands. In this study, the author used a quantitative method, then the available data was processed using the IBM SPSS Statistic 19 application. In obtaining the data, the researcher used 338 respondents, namely consumers who had visited the Prata Waroeng 8 Tiban business. The author also conducted observations, documentation, distributed questionnaires and conducted direct interviews with the owner of Prata Waroeng 8 to obtain information about the place where the research was conducted. The results of this study are that the variety of menus affects consumer satisfaction and the quality of food affects consumer satisfaction. Then the variety of menus and food quality simultaneously affect consumer satisfaction